The Implementation of Podcast Audio on Teaching Listening comprehension - Aries Fachriza (International Journal of English Learning and Applied Linguistics (IJELAL), 2020)
Podcasting is being introduced into academic fields as an e-learning tool. The existance of podcasting contributes to help teaching learning activities running well. However, there were difficulties for the students to attain the meaning in listening subject. It was because that listening comprehension is becoming complex process to comprehend spoken language on English Foreign Language learner. This study aimed to investigate the use of audio podcast in achieving listening skill in teaching activities. This study  conducted  as library research using systematic reviews method to find the effectiveness of audio podcast  in teaching listening on all level of students. According to literature reviews, this study revealed the use of audio podcast in teaching listening is effective for the students both in classroom and  out door class